PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PT GUDANG DARAM TBK PERIODE 2013-2020 - Rian Adrian (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of financial performance on the stock price of PT. Gudang Garam Tbk for the 2013-2020 period. The population in this study is the all financial report of PT Gudang Garam Tbk, with sample of the financial statements of PT Gudang Garam Tbk, for the last eight years (2013-2020). The technique of data collection is done by documentation technique. The analysis used is the classical assumption test (normality, autocorrelation, multicollinearity and heteroscedasticity), then hypothesis testing using t-test and f-test. The results of this study explain that Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Return On Equity variables have no partial effect on stock prices. Then based on the simultaneous testing of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Return On Equity variables have no simultaneous effect on stock prices